1990
DOI: 10.1111/j.1479-828x.1990.tb03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking, Urinary Cotinine Levels and Birth‐Weight

Abstract: The smoking habits of 300 consecutive pregnant women and of other members of their household were obtained by interview at 16 and 32 weeks' gestation and after delivery. Urine samples for estimation of cotinine were collected at the same times during pregnancy and on admission in labour. Both self-reports of active maternal smoking and urinary cotinine levels were significantly associated with lighter babies but urinary cotinine correlated the better. Active maternal smoking was associated with a decrease in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…This observation has implications for the use of cotinine as a biomarker for cigarette smoking during pregnancy. Our data do not affect the validity of cotinine levels as a predictor of pregnancy outcomes, which are based on empirical observations (Mathai et al, 1990;Bardy et al, 1993;Li et al, 1993;Ellard et al, 1996). But our study does indicate that the lower cotinine levels observed in smokers during pregnancy compared with the same individuals before or after pregnancy do not necessarily reflect less smoke exposure.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This observation has implications for the use of cotinine as a biomarker for cigarette smoking during pregnancy. Our data do not affect the validity of cotinine levels as a predictor of pregnancy outcomes, which are based on empirical observations (Mathai et al, 1990;Bardy et al, 1993;Li et al, 1993;Ellard et al, 1996). But our study does indicate that the lower cotinine levels observed in smokers during pregnancy compared with the same individuals before or after pregnancy do not necessarily reflect less smoke exposure.…”
Section: Discussionmentioning
confidence: 60%
“…Among pregnant smokers, maternal levels of cotinine correlate better with outcome measures such as birth weight than the number of cigarettes smoked per day (Haddow et al, 1987;Mathai et al, 1990;Bardy et al, 1993;Li et al, 1993;Ellard et al, 1996;Klebanoff et al, 1998;SeckerWalker et al, 1998). Recently, a study of women during pregnancy and again postpartum found that during pregnancy the median saliva cotinine concentration per cigarette was 3.5 ng/ml versus 9.9 ng/ml when not pregnant (Rebagliato et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This, and a number of studies, have found a closer dose -e¡ect relationship between birthweight de¢cits and nicotine metabolite levels in serum and urine than with self-reported cigarette consumption. 7,8 Serum cotinine concentration at 16 weeks'gestation was also found to have a high positive predictive value for small-for-gestational age deliveries, which was double that for self-reported smoking habit and independent of associated maternal characteristics. 9 This led to the recommendation that Original Article biochemical veri¢cation of self-reported quitting is essential to the evaluation of smoking cessation interventions and may be a useful predictor of poor pregnancy outcome.…”
Section: Introductionmentioning
confidence: 88%
“…In the first reports, exposure assessment was based only on information on the spouse's smoking (5)(6)(7)9,(11)(12)(13)(15)(16)(17)21,22,24,26). Later studies collected information on multiple sources, such as other family members and work exposure or on quantity measured as daily duration of exposure or number of cigarettes smoked indoors (10,(18)(19)(20)25,31).…”
mentioning
confidence: 99%